Effect of a partial saturation on the hydromechanical response of a clay rock - Delage, Pierre; Menaceur, Hamza; Belmokhtar, Malik; Talandier, Jean (Journal of Applied Engineering Science & Technology, 2016)
The behaviour of claystones and shales ispresently investigated in details in link with their potential use as host rock for radioactive waste disposal at great depth. Claystones are very sensitive to changes in water content, with an increase of their mechanical properties with desaturation under increased suction. Claystones have standard water retention properties but some effect of hydric damage is observed after a drying-wetting cycle that results in enhanced swelling. The microstructure of the Callovo-Oxfordian claystone tested here is characterized by a clay matrix (50% clay fraction) made up of clay platelets that can be assimilated to bricks. The pore size distribution is well organized around a mean diameter of 32nm that provides an idea of the mean thickness of the platelets. A stress release at constant water content results in a swelling and desaturation due to an internal transfer from free inter-platelets water to linked intra-platelets water.